2017
DOI: 10.1136/jfprhc-2016-101492
|View full text |Cite
|
Sign up to set email alerts
|

Incarceration and exposure to internally displaced persons camps associated with reproductive rights abuses among sex workers in northern Uganda

Abstract: These results suggest a critical need for removal of legal and social barriers to realising the SRH rights of all women, and ensuring safe, voluntary access to reproductive choice for marginalised and criminalised populations of FSWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This study adds to the limited body of evidence describing the health and social inequities faced by conflict-affected women engaged in sex work and to our knowledge remains one of few studies reporting on the HIV ‘cascade of care’ among conflict-affected SWs in sub-Saharan Africa. 3032,34 Over one-third of SWs living with HIV were newly diagnosed infections, which is higher than a recent study in Malawi (20%) 35 and lower than a study in Zimbabwe in which half of SWs with confirmed HIV infection were unaware of their status, with the majority not on ART. 8 Women reporting unstable housing and substance use were more likely to be newly diagnosed, whereas accessing condom demonstrations and greater number of lifetime pregnancies were protective, likely reflecting linkage to HIV testing and care services through accessing SRH and condom promotion services.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This study adds to the limited body of evidence describing the health and social inequities faced by conflict-affected women engaged in sex work and to our knowledge remains one of few studies reporting on the HIV ‘cascade of care’ among conflict-affected SWs in sub-Saharan Africa. 3032,34 Over one-third of SWs living with HIV were newly diagnosed infections, which is higher than a recent study in Malawi (20%) 35 and lower than a study in Zimbabwe in which half of SWs with confirmed HIV infection were unaware of their status, with the majority not on ART. 8 Women reporting unstable housing and substance use were more likely to be newly diagnosed, whereas accessing condom demonstrations and greater number of lifetime pregnancies were protective, likely reflecting linkage to HIV testing and care services through accessing SRH and condom promotion services.…”
Section: Discussionmentioning
confidence: 64%
“…alcohol/drug use, inconsistent condom use with clients, intimate partners); and structural factors, including housing, migration history, current places of servicing clients (e.g. bar/club, lodge, hotel, highway/truckstop, clients, own place); intimate partner violence; 32 workplace violence by clients, police, and military; policing and criminalization (e.g. arrest, incarceration); and conflict-related exposures (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, those who sold sex also had greater odds of receiving recent psychological treatment, which was in the opposite direction of the hypothesis. Perhaps the finding may be explained by the fact PLWH who trade sex often face greater trauma or mental health diagnoses than those who don’t trade sex [6567]. Studies show a high prevalence of mental health disorders among harder-to-reach persons living with HIV, and that poorer mental health was associated with sexual violence and stigma experiences [68], experiences also heightened by involvement in the sex trade.…”
Section: Discussionmentioning
confidence: 99%